AI IN LANGUAGE LEARNING - Tilavmurodova Lola Bahriddin qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
Artificial Intelligence (AI) is changing the way people learn languages by providing smart, interactive, and personalized tools. AI technologies like natural language processing and speech recognition help learners improve pronunciation, grammar, and vocabulary. With chatbots and language apps, learning becomes more flexible and engaging.